Expressing Political Opinions in Hip Hop Music - Gabrielová, Kateřina (Univerzita Pardubice, 2014)
The aim of the thesis is to display rap music as a source of information which apprises of political and social issues in association with Afro-Americans. As primary sources are used lyrics of rap songs focusing on themes of stereotypes, the Obama era, slavery, racism, and social and racial equity.
Vyjadřování politických názorů v hip hopové hudbě
Keywords: hip hop culture; hip hop music; rap; conscious rap; stereotypes; racism; social equity; hip hopová kultura; hip hopová hudba; rap; conscious rap; stereotypy; rasismus; sociální rovnost